Occurrence of comorbidity with colorectal cancer and variations by age and stage at diagnosis. (October 2022) - Gheybi, Kazzem; Buckley, Elizabeth; Vitry, Agnes; Roder, David
Abstract: Background: While age and stage at diagnosis are known to affect treatment choices and survival from colorectal cancer (CRC), few studies have investigated the extent to which these effects are influenced by comorbidity. In this study, we describe the occurrence of comorbidity in CRC cases in South Australia and associations of comorbidity with age, stage and the age-stage relationship. Furthermore, we report on the association of individual comorbidities with age and stage at diagnosis. Methods: The South Australian Cancer Registry (SACR) provided CRC data (C18-C20, ICD-10) for 2004–2013 diagnoses. CRC data were linked with comorbidity data drawn from hospital records and health insurance claims. Logistic regression was used to model associations of comorbidity with age and stage. Results: For the 8462 CRC cases in this study, diabetes, peptic ulcer disease, and previous cancers were the most commonly recorded co-existing conditions. Most comorbidities were associated with older age, although some presented more frequently in younger people. Patients at both ends of the age spectrum (<50 and 80 + years) had an increased likelihood of CRC diagnosis at an advanced stage compared with other ages (50–79 years old). Adjusting for comorbidities moderated the association of older age with advanced stage. Conditions associated with advanced stage included dementia (OR = 1.25 (1.01–1.55)), severe liver disease (OR = 1.68 (1.04–2.70)), and a previous cancer (OR = 1.18 (1.08–1.28)). Conclusion: Comorbidities are prevalent with CRC, especially in older people. These comorbidities differ in their associations with age at diagnosis and stage. Dementia and chronic heart failure were associated with older age whereas inflammatory bowel disease and alcohol access were associated with younger onset of the disease. Severe liver disease and dementia were associated with more advanced stage and rheumatic disease with less advanced stage. Comorbidities also interact with age at diagnosis and appear to vary the likelihood of advanced-stage disease. CRC patient have different association of age with stage depending on their comorbidity status. Highlights: Most comorbidities are more likely to be present in older CRC cases. Cases at both ends of the age spectrum tend to have more advanced stages. Comorbidities weaken the association of older age with advanced stage of CRC. Dementia, liver disease and previous cancer are associated with advanced stage CRC.